1986
DOI: 10.1080/07435808609035430
|View full text |Cite
|
Sign up to set email alerts
|

The Apparent Shift in Distribution of Aromatase Activity in the Subcellular Fraction of Human Term Placenta Stored At -96°C

Abstract: The effects of storage at -96 degrees C on the distribution of the total aromatase activity in the homogenate, 900 xg pellet and 900 xg supernatant of two human term placentas were studied. Both specific and total aromatase activities in the 900 xg pellet increased through storage at -96 degrees C, while that in the 900 xg supernatant decreased. The ratio of total aromatase activity between the 900 xg pellet and 900 xg supernatant was about 2:1 in fresh placenta, but the ratio was about 19:1 in placenta stored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

1987
1987
2006
2006

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
2
2
0
Order By: Relevance
“…Prolonged freezing, possibly in combination with subsequent thawing, apparently disrupted the association of ASPA with myelin by an as-yet-undetermined mechanism. Similar shifts in subcellular distribution have been reported for other membrane proteins following prolonged freezing of brain (Stahl and Swanson 1975) and other tissue (Tochigi et al 1986). However, it may be noted that the association of ASPA with myelin from unfrozen brain proved strong enough to survive treatment with 0.5 mol/L NaCl and 0.1% Na-taurocholate ( Fig.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Prolonged freezing, possibly in combination with subsequent thawing, apparently disrupted the association of ASPA with myelin by an as-yet-undetermined mechanism. Similar shifts in subcellular distribution have been reported for other membrane proteins following prolonged freezing of brain (Stahl and Swanson 1975) and other tissue (Tochigi et al 1986). However, it may be noted that the association of ASPA with myelin from unfrozen brain proved strong enough to survive treatment with 0.5 mol/L NaCl and 0.1% Na-taurocholate ( Fig.…”
Section: Discussionsupporting
confidence: 83%
“…Prolonged freezing, possibly in combination with subsequent thawing, apparently disrupted the association of ASPA with myelin by an as‐yet‐undetermined mechanism. Similar shifts in subcellular distribution have been reported for other membrane proteins following prolonged freezing of brain (Stahl and Swanson 1975) and other tissue (Tochigi et al. 1986).…”
Section: Discussionsupporting
confidence: 82%
“…Placental aromatase activity (2.8 ± 0.5 pmol/min.mg) is comparable to activities reported for other mammals but is only 10% of the values found in human term placentae. Tochigi et al [1986] reported aromatase activity ranging from 39-51 pmol/min.mg in homogenates of human placentae. Both sheep (1.4 pmol/min.mg) [France et al, 1987] and pig (5.4 pmol/min.mg) [Corbin et al, 1995] aromatase activities in placental homogenates are in the same range as the primate values reported here.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the pelleted fraction was used in subsequent experiments. Although lower in specific activity, the 900 x g pellet contained most of the aromatase activity of human term placenta (29). The concentration-dependent inhibition by 60-BrA was then investigated.…”
Section: Resultsmentioning
confidence: 99%